2017 IEEE International Conference on Image Processing (ICIP) 2017
DOI: 10.1109/icip.2017.8296329
|View full text |Cite
|
Sign up to set email alerts
|

Blind image deblurring using class-adapted image priors

Abstract: Blind image deblurring (BID) is an ill-posed inverse problem, usually addressed by imposing prior knowledge on the (unknown) image and on the blurring filter. Most of the work on BID has focused on natural images, using image priors based on statistical properties of generic natural images. However, in many applications, it is known that the image being recovered belongs to some specific class (e.g., text, face, fingerprints), and exploiting this knowledge allows obtaining more accurate priors. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Ljubenovic et al proposed a method that estimates the original images and the motion blur using minimum mean squared error (MMSE) estimators, which are based on the alternating direction method of multipliers (ADMM) and a Gaussian mixture model (GMM). They verified the performance of the method using fingerprint images [19]. Lopez et al attempted motion deblurring using an ensemble neural network and fuzzy methods rather than using an estimation function.…”
Section: Related Workmentioning
confidence: 96%
“…Ljubenovic et al proposed a method that estimates the original images and the motion blur using minimum mean squared error (MMSE) estimators, which are based on the alternating direction method of multipliers (ADMM) and a Gaussian mixture model (GMM). They verified the performance of the method using fingerprint images [19]. Lopez et al attempted motion deblurring using an ensemble neural network and fuzzy methods rather than using an estimation function.…”
Section: Related Workmentioning
confidence: 96%
“…Teodoro et al propose using a Gaussian mixture model as a class-specific patch-based prior, for solving two image inverse problems, namely non-blind deblurring and compressive imaging [45]. In prior work, we have shown that class-specific GMM-based image prior can be used for BID [27]. That approach allows handling situations where the image being processed contains regions of different classes, as done by Teodoro et al for denoising and non-blind deblurring [44].…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…In particular, we use denoisers based on Gaussian mixture models (GMM) or dictionaries, learned from patches of clean images from specific classes. These types of denoisers can be used for images that contain only one class, as presented in [27], or two or more classes [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest class-specific approach to our work is the one proposed in [26], [27], [28], [29]. It shows improvement in image restoration tasks (denoising and deblurring) by adapting the reconstruction algorithm to a specific class of images.…”
Section: Related Workmentioning
confidence: 99%